OPTIMASI PENGGUNAAN SEDIMENT TRAP PADA ALUR PELAYARAN BARAT SURABAYA MENGGUNAKAN PEMODELAN TRANSPOR SEDIMEN (STUDI KASUS: ALUR PELAYARAN BARAT SURABAYA, JAWA TIMUR) - Pratomo, Danar Guruh; Aziz, Muhammad Rinaldi Fauzan; Aziz, Muhammad Rinaldi Fauzan (Geoid, 2020)
Tanjung Perak Port is one of the largest ports in Indonesia that is quite strategic for economic development and sea transportation. The handling of shipping lanes is needed so that ship traffic remains stable. The research location in Alur Pelayaran Barat Surabaya with 3 different conditions namely Pre-Survey, Post-Survey condition 1 has a sediment trap and Post-Survey condition 2 has no sediment trap. Research uses 3D modeling to see hydrodynamic activity. The results of modeling are current patterns, which will influence the pattern of sediment distribution in the study area. The model is formed based on the parameters of tides, river discharge, and wind in the study area. Tidal Pre-Survey has a value of RMSE and MAE of 0.0307 meters and 0.0244 meters with a current of 0.3 m/s. Post-Survey condition 1 has a value of 0.0336 meters and 0.0276 meters with a current of 0.2 m/s. Post-Survey condition 2 has a value of 0.0563 meters and 0.0289 meters with a current of 0.4 m/s. The pattern of sediment distribution between Post-Survey conditions 1 and condition 2 has the same dominant value starting from -0.005 meters to 0.0175 meters. Maximum value of condition 1 is 0.072 meters while condition 2 is 0.062 meters in sediment trap area. Even though condition 1 has a maximum value greater than condition 2, it occurs at just a few points.